Selection of nitrogen source affects the growth and metabolic enzyme activities of Chlorella vulgaris (Beijerinck) strain R-06/2 (Chlorophyta) - Vasileva, Ivanina A.; Ivanova, Juliana G.; Gigova, Liliana G. (Archives of Biological Sciences, 2020)
Paper description: Growth and nitrogen metabolizing enzyme responses of microalgae to changes in the nitrogen source have been characterized well only when ammonium is replaced by nitrate or nitrate by ammonium. We investigated the simultaneous effect of cultivation time and three different nitrogen sources on the growth rate, biochemical composition and activity of six metabolic enzymes of Chlorella vulgaris R-06/2. The results showed the strain is tolerant, maintaining efficient metabolic enzyme functions and good growth under all studied cultivation conditions. This work helps to better understand algal metabolism and the increment in production of low-cost nutritional biomass. Abstract: The choice of nitrogen source in a cultivation medium can specifically affect the physiology and biochemistry of microalgae. To increase the production of low-cost valuable biomass, the preferred nitrogen form for each alga should be determined. The aim of our study was to analyze the effects of different nitrogen sources and cultivation times on the growth, biochemical composition and the activities of glutamine synthetase, glutamate synthase, glutamate dehydrogenase, malate dehydrogenase, aspartate aminotransferase and proteases of Chlorella vulgaris R-06/2. Media supplemented with urea or ammonium nitrate provided similarly (p>0.05) high growth rates for a short cultivation time (4 days). The two nitrogen compounds applied simultaneously ensured better biomass yield but for prolonged cultivation. In the exponential growth phase, ammonium nitrate stimulated (p<0.05) protein production, whereas urea enhanced (p<0.05) the carbohydrate content in older cultures as compared to the other nitrogen sources. The activity of each of the studied metabolic enzymes of C. vulgaris R-06/2 varied specifically depending on the nitrogen source and the growth phase, ensuring the maintenance of efficient, balanced metabolism under all cultivation conditions. When using large-scale cultivation to produce biomass for various useful applications, the selection of nitrogen source should be based on algal metabolism. https://doi.org/10.2298/ABS200219023V Received: February 19, 2020; Revised: April 27, 2020; Accepted: May 6, 2020; Published online: May 13, 2020 How to cite this article: Vasileva IA, Ivanova JG, Gigova LG. Selection of nitrogen source affects the growth and metabolic enzyme activities of Chlorella vulgaris (Beijerinck) strain R-06/2 (Chlorophyta). Arch Biol Sci. 2020;72(2):291-300.